THE ISLAMIC CIVILIZATION OF THE ABBASID DAULA PERIOD IN INCREASING THE INTEREST OF READING SOCIETY (IN THE DIGITAL LITERACY ERA) - Makrufi, Anisa Dwi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This paper aims to analyze the strategy of the Abbasids in improving literacy activities in the society. In this study, analyses on the relevant literature have been carried out. As a result, the Abbasid Daula had a huge contribution to the development of science, which could not have been achieved without reading from the people and scientists of that time. Bayt al-Hikmah as the largest library in the world in the era became the historical evidence of the glory of Islam, through reading activity. Reading is a very positive activity that is very influential in human life, how to look at something; set options; differentiate good and bad and how humans behave are often influenced by the understanding of science from an activity, that is reading. However, this is inversely related to data showing that Indonesian reading culture is ranked at the lowest among Asian countries. Seeing the phenomenon that occurs, Indonesia as a majority Muslim society should be able to learn from the history of Islamic civilization in the past. The strategies undertaken by the caliphs of Abbasid Daula in increasing literacy, such as: the government should enlarge the education budget to improve the quality of human resources; establishing libraries, especially for remote, deepest, and outermost areas; active in the translation of works in the field of religion and science; the author is given a reasonable reward for the work he wrote; and finally the government should pay great attention to scientists and humanists. In the digital age, as it is today, reading is certainly not something stiff. Wherever and whenever humans are facilitated by the name technology in accessing the reading they need. Whether it's content that is positive or negative, like the word all available in the hands of humans.